2017
DOI: 10.1111/ilr.12069
|View full text |Cite
|
Sign up to set email alerts
|

Youth earnings and labour market volatility in Europe

Abstract: The authors provide new evidence on youth earnings and labour market volatility, including flows into and out of employment, across Europe during the Great Recession. EU-SILC data for the period 2004-13 reveal large disparities in volatility levels and trends across European countries. As expected, the Great Recession increased youth labour market volatility, offsetting the trends observed over the previous years of economic prosperity. A variance decomposition exercise points to greater exposure to worker tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Our findings at least do not support the counterargument that in countries where job stability is low, jobhopping may serve less as a signal for recruiters than in countries with lower labour market volatility. Indeed, Ayllón and Ramos (2017) have found that levels of labour market volatility, which they measured in terms of changes in wages and transitions into and out of employment, are higher in Bulgaria and Greece than in Norway (the Swiss case was not included in their study). It is therefore reasonable to assume that, whereas unemployment can occur through no fault of one's own in contexts with high unemployment (and is therefore of little information value for recruiters), job-hopping is less likely to be interpreted as a consequence of the overall economic situation or as beyond the applicant's control.…”
Section: Job-hoppingmentioning
confidence: 99%
“…Our findings at least do not support the counterargument that in countries where job stability is low, jobhopping may serve less as a signal for recruiters than in countries with lower labour market volatility. Indeed, Ayllón and Ramos (2017) have found that levels of labour market volatility, which they measured in terms of changes in wages and transitions into and out of employment, are higher in Bulgaria and Greece than in Norway (the Swiss case was not included in their study). It is therefore reasonable to assume that, whereas unemployment can occur through no fault of one's own in contexts with high unemployment (and is therefore of little information value for recruiters), job-hopping is less likely to be interpreted as a consequence of the overall economic situation or as beyond the applicant's control.…”
Section: Job-hoppingmentioning
confidence: 99%
“…Third, evidence of earnings constitutes an important database of information for university candidates and HEIs. Owing to such information, young people with market-oriented education goals can make more informed decisions about higher education (Ayllón, Ramos 2019). On the other hand, HEIs can utilise the data to revamp those curricula that are aimed at training employable graduates and ensure that the 'investment' in higher education yields the highest return possible (Belfield, Bailey 2019).…”
Section: Introductionmentioning
confidence: 99%